A theory of economic growth : dynamics and policy in overlapping generations - De la Croix, David, 1964- (Cambridge University Press, 2002)
This book provides an in-depth treatment of the overlapping generations model in economics incorporating production. Methodological emphasis is put on using general preferences and technologies, on the global study of dynamic aspects of the model, and on furnishing adequate tools to analyze policies involving inter-generational transfers.